Bridging Across Language Divide for Growth and Peaceful Coexistence: A Panacea for Economic Recession in a Multilingual Nigeria - Akinwamide, Timothy Kolade (Budapest International Research and Critics University, 2018)
Language – a human phenomenon, which is the basic means of communication among the world citizens has generated ‘a great divide’ as a result of non understanding of terms, patters and words in different languages of the world. Our cultural heritages are expressed basically in our languages. This aptly explains the balkanizations of peoples along political, religious and economics interests. The aftermath of this divide is often seen in internecine and socio-economic doldrum with the attendant effect of poverty. This paper is advocating for bridging across our language divides - minority and majority languages - to connect us to the inherent dividends in a multilingual society. It is believed that no society stands in isolation in the bid to achieve overall success for her citizens. The colonial masters did not understand our languages yet they came, explored, extracted and made exploits from the flora and fauna in the terrain of Africa continent. There are lot of economic benefits that are available in the vast land of Africa which language divides have buried beyond our reach.